Report of the director-general - International Labour Organisation. African Regional Conference; International Labour Office (Geneva : International Labour Office, 1993)
"A single consolidated report covering the various topics to be considered by the Conference," prepared in advance of the conference by the International Labour Office.
Report I (Part I)-1983. Social aspects of development in Africa : The role of social institutions. Report I (Part II)-1983. Application of the declaration of principles and programme of action of the World Employment Conference -- Report II-1988. Rural and urban training in Africa -- Report III-1988. Co-operatives : a review of co-operative development in the African region : scope, impact and prospects.
A record of proceedings of the conference is published separately.
SERBIB/SERLOC merged record
Keywords: Labor -- Africa -- Congresses; Labor unions -- Africa -- Congresses; Industrial relations -- Africa -- Congresses; Industrial relations; Labor; Labor unions; Africa; Congresses; Conference papers and proceedings